Culture and compensation interaction: how do financial rewards affect public sector engagement? - Dickson Mdhlalose; Thokozani Mtshali (Veredas do Direito, 2026)
Cultural research on the influence of individuality and collectivism on employee engagement is lacking. This study aims to analyse the impact of employee financial rewards on employee engagement, focusing on individualistic and collectivistic cultures as moderating variables in a public sector organisation. This research employed standardised face-to-face open-ended interviews. The research instrument is based on a single theme and comprises five open-ended questions to address the objectives of this study. The constant comparative data analysis approach was employed in conjunction with content analysis. The researchers categorised the data based on their disparities and similarities. This study found that the municipality offers its employees financial rewards; however, due to inequality, unfairness, favouritism, and political influence, employees are not rewarded fairly, leading to unhappiness and disengagement from their work and the organisation. The municipality does not practice either a collectivistic or an individualistic culture. A poor imbalance between individualistic and collectivistic cultures reduces the impact of financial rewards on employee engagement. This study's findings emphasise that the effectiveness of financial rewards on employee engagement depends on the organisation's practices and the equilibrium of individualistic and collectivistic cultures.
Keywords: J45; M52; Z13; O15; M12; 330; Culture; Employee Engagement; Financial Rewards; Public Sector